THE INFLUENCE OF CONSUMER ETHNOCENTRISM AND PERCEIVED VALUE ON PURCHASE DECISION OF LOCAL SHOE IN STUDENT ENVIRONMENT - Pratminingsih, Sri Astuti; Astuty, Eriana (Jurnal Aplikasi Manajemen, 2017)
Companies in Indonesia are currently facing fierce competition as more competitors enter Indonesia. To win the competition, the local companies have to pay attention to consumer behavior in buying a product. Factors that influence purchase decision of local products include consumer ethnocentrism and perceived value. The objective of this study is to investigate how consumer ethnocentrism and perceived value influence purchase decisions. This research uses descriptive research. Data were collected through a survey by distributing questionnaires to 200 respondents and returning as many as 197 respondents. The results of the study indicate a positive influence between ethnocentrism consumers on purchasing decisions of the local shoe. Perceived value also significantly influence purchasing decisions and perceived value proved to moderate the relationship between ethnocentrism consumers and purchasing decisions.